Problematika Penerjemahan Novel-Novel Indonesia Masa Hindia-Belanda Konteks Dan Persepsi Budaya - Ida Sukowati; Mu'minin Mu'minin (IKIP Budi Utomo Malang, 2022)
This research is motivated by the fact that the reinterpretation of a text from the source language into the target language has not been fully carried out properly to produce a translation that has a content of meaning and sense of value commensurate with the original text in the source language. Likewise in translating literary works, a translator is also required to have the ability to understand the cultural content contained in a source text. The research method used is descriptive qualitative with procedures for identifying the structure and content of the novel and reading figuratively using identification with the pragmatic context of the novel. Careless translators do not occur, including by considering the understanding of the procedures for identifying the structure and content of the translated literary works, understanding of the pragmatic and semantic context of the translated literary works, and understanding of the cross- cultural understanding of the translated literary works.